Support for refugees declines when helpers have unequal positions and abilities to help. - Van Steenvoort, Milan; Rusch, Hannes; Böhm, Robert; van Lange, Paul A.M. (Journal of Ethnic & Migration Studies, 2026)
Refugees' well-being hinges on receiving adequate support throughout their journey. In 2015, as many refugees migrated toward wealthier Northern and Western Europe, it seemed like communities' willingness to offer help depended not only on refugees' attributes or individual benevolence but also on communities' positions along the route and their economic status. However, survey methods struggle to isolate these factors' causal effects. We therefore use a framed economic experiment to manipulate specific situation features while keeping others constant. In our stylised economic game, two groups of four citizen players (n = 910) decide on aiding a passive refugee player (n = 114). One group (early-positioned) decides before the other (late-positioned). We introduce economic inequality by varying the groups' endowments (low vs. high). Our findings show that unequal endowments harm refugee support, and late-positioned citizens base their support on early-positioned citizens' actions. These results from our stylised setup suggest that support for refugees depends on macro-level situational factors beyond individual attitudes. From a policy standpoint, addressing economic disparities between communities involved in refugee support and eliminating sequential decision-making through appropriate institutions could enhance support for refugees.